Pengaruh Citra Perusahaan, Kemudahan, dan Kegunaan terhadap Intensi Generasi Z Membuka Rekening Syariah: Studi pada Generasi Z Jakarta Selatan - Zakia Ayu Permata; Akhmad Edhy Aruman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of company image, perception of ease of use, and perception of usability on the behavioral intentions of Generation Z in using online sharia savings services through Maybank Indonesia's M2U ID application. The background of this research is based on the low adoption rate of Islamic banking services in Indonesia, although the younger generation, especially Generation Z, shows a high level of digital literacy and technology use. This study uses a quantitative approach with an explanatory method. Data was collected from 139 respondents who were residents of South Jakarta aged 18–25 years old through purposive sampling techniques. The research instrument was a closed-ended questionnaire with a five-point Likert scale, which included four main constructs: company image, perception of ease of use, perception of usability, and behavioral intent. Data analysis was carried out using multiple linear regression to test the relationships between variables. The results of the study show that the company's image and the perception of ease of use have a positive and significant influence on the behavioral intention of opening an online sharia savings account. On the contrary, the perception of usefulness actually shows a significant negative influence on behavioral intent. These findings indicate that although functional features are important, symbolic factors and value perception are more dominant in shaping digital sharia service adoption decisions. The implications of this study suggest that Islamic financial institutions need to emphasize on building a strong brand image and creating an easy and intuitive user experience. In addition, it is important to reinforce religious and ethical values in marketing communication and product development. The study also highlights that the alignment between sharia values and digital-native consumer preferences can be key in increasing the market penetration of Islamic financial services.